Pengaruh Kompensasi Dan Kesejahteraan Pegawai Terhadap Kinerja Pegawai Dengan Semangat Kerja Sebagai Variabel Intervening Pada Puskesmas Gunung Di Kota Padang Panjang - Diky Setiawan; Emil Salim; Olandari Mulyadi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of compensation and employee welfare on employee performance, with work morale serving as an intervening variable, at the Gunung Community Health Center (Puskesmas) in Padang Panjang City. The study employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 software for analysis. The study population and sample consist of employees from the Gunung Community Health Center in Padang Panjang City. The results indicate a positive and significant influence of compensation on work morale and a positive and significant influence of employee welfare on work morale. There is a positive but insignificant influence of compensation on employee performance, whereas employee welfare has a positive and significant influence on employee performance. Work morale has a positive and significant influence on employee performance. Furthermore, the study finds a positive but insignificant influence of compensation on employee performance mediated by work morale, and a positive and significant influence of employee welfare on employee performance mediated by work morale.